Reichard'̊s Passagier auf der Reise in Deutschland und der Schweiz, Holland und Belgien, nach Paris, London, Kopenhagen, Stockholm, St. Petersburg, Warschau, Pesth, Venedig, Mailand, Turin und Genua. T. 3, Süddeutschland, Tyrol, Ober-Italien und Oesterreich, Reise nach Krakau, Offen und Pesth. - Reichard, Heinrich August Ottokar (1751–1828). Autor; Herbig, Ad. Redaktor; Verlag von F. A. Herbig. Wydawca (Verlag von F. A. Herbig, 1859)
Siebzehnte Auflage, nach eigenen Anschauungen und den besten Quellen neu bearbeitet / Herausgegeben von Ad. Herbig
XIV, 300 stron, [10] kart tablic złożonych, [11] karta tablic : ilustracje ; 18 cm
Indeks
Keywords: South Germany; Salzburg; Tirol; North Italy; Wien; Styria; Praha; Cracow; Budapest; guidebooks

M 34 - SW Mährisch- Ostrau (Justus Perthes, 1943)
Scale 1:500 000 Bonnesche unechte Kegelprojektion
1 map : color ; 46 x 46 cm, on sheet 56 x 54 cm
Keywords: topographic map; aerial maps; Ostrava (Czechia; region); Nowy Sącz region; Nitra (Slovakia; region); Miskolc (Hungary; region)

N 33-SW Berlin (Justus Perthes, 1944)
Scale 1:500 000 Bonnesche unechte Kegelprojektion
1 map : color ; 46 x 42 cm, on sheet 55 x 56 cm
Keywords: topographic maps; aerial maps; Demmin (Germany; region); Szczecin Lagoon; Berlin (Germany; region); Brandenburg (Germany; region)

Tydzień na wodach Morza Egejskiego - Zych, Franciszek (1853– ). Autor; Spółka Wydawnicza Polska (Kraków). Wydawca (Spółka Wydawnicza Polska, 1896)
51 pages ; 21 cm
Osobne odbicie: "Przeglądu Polskiego", z m. lutego 1896
Keywords: travels; geographical descriptions; Greece; Aegean Sea; islands; Aegean Islands

The processes of depopulation of rural areas in Central and Eastern Europe : proceedings of the International Seminar on Rural Depopulation, Szymbark, Poland, September 1989 - Stasiak, Andrzej (1928–2008). Red.; Mirowski, Włodzimierz (1927– ). Red. (IGiPZ PAN, 1990)
322 pp. : maps. ; 24 cm
Bibliogr.
Keywords: rural areas; rural population; depopulation; Central Europe; Eastern Europe

Environment of the Sant valley (southern Khangai Mountains) : results of the Polish-Mongolian Physico-Geographical Expedition. Vol. 2 = Prirodnaâ sreda doliny Sant (ûžnyj Hangaj) - Starkel, Leszek (1931– ). Ed.; Kowalkowski, Alojzy. Ed. (IGiPZ PAN, 1980)
87, [16] pp., [12] p. pl., [2] l. pl. : phot., maps ; 24 cm
Vol. 1 under the title: Vertical zonality in the southern Khangai Mountains (Mongolia)
Bibliogr. p. [79]-82
Summ. rus.
Keywords: natural environment; geomorphology; natural environment dynamics; typology of geoecosystems; expeditions; Polish-Mongolian expeditions; Mongolia; Khangai Mountains

General Charte von Ungarn : mit seinen Nebenländern Croatien, Dalmatien, Slavonien und Siebenbürgen, ingleichen Gallizien und der Bukowina nebst den angrenzenden Provinzen des Osmannischen Reichs & cc. - Güssefeld, Franz Ludwig (1744–1808) (bey den Homannischen Erben, 1796)
Scale [ca 1:3 300 000]
1 map : copperplate engraving, hand col. ; 49x57 cm
Prime meridian Ferro
Keywords: political-administrative maps; chorographic maps; Hungary; Galicia (Austro-Hungary); Bukovina; Balcans; 18th century

Tabula Marchionatus Brandenburgici et , Ducatus Pomeraniæ quæ sunt Pars Septentrionalis Circuli Saxoniæ Superioris - Homann, Johann Baptist (1664–1724) (edita a Ioh Baptista Homanno, 1715)
Skala [ca 1:1 000 000], podziałka liniowa: Milliaria germanica communia
1 mapa : miedzior. kolor. ręcznie. ; 48x54 cm
Południk Ferro określony po obliczeniu współrzędnych przez katalogującego
Kartusz w formie draperii unoszonej przez putta, u dołu kartusza putta trzymające herby Brandenburgii i Pomorza zwieńczone koroną królewską
W prawym dolnym rogu podziałki wpisane w parergę w formie postumentu, na której siedzi putto z cyrklem w ręku
Keywords: chorographic maps; political-administrative maps; Mecklenburg-Vorpommern; West Pomerania; Brandenburg (Germany); 18th century

Nazwy fizjograficzne Ameryki Południowej, Australii i Oceanii, Antarktydy oraz nazwy fizjograficzne mórz i oceanów świata - Ratajski, Lech (1921–1977). Oprac.; Szewczyk, Janina. Oprac. (IGiPZ PAN, 1955)
40 s. ; 28 cm
Keywords: geographical names; Polish geographical names; South America; Australia; Oceania; Antarctica

Nazwy fizjograficzne Grenlandii, Ameryki Północnej i Środkowej oraz nazwy miast od 50-100 tys. mieszkańców dla Ameryki Północnej, Środkowej, Południowej, Australii i Nowej Zelandii - Ratajski, Lech (1921–1977). Oprac.; Szewczyk, Janina. Oprac.; Tyszkiewicz, Wiesława (1932– ). Oprac. (IGiPZ PAN, 1955)
Keywords: geographical names; Polish geographical names; North America; Central America; Greenland

Superioris et Inferioris Ducatus Silesiæ In Suos XVII Minores Principatus Et Dominia Divisi Nova Tabula - Homann, Johann Baptist (1664–1724) (Ioh. Baptista Homa[n]no, 1712)
Skala [ca 1:750 000], podziałka liniowa: Scala Millitaria communia Germanica
1 mapa : miedzior. kolor. ręcznie ; 49x58 cm, na ark. 55x64 cm
W górnym prawym rogu mapy na zwoju umieszczony plan Wrocławia z napisem Breslau
Opisano strony świata: Septentrio, Oriens, Meridies, Occidens
Tyt. w kartuszu w dolnym lewym rogu mapy, umieszczony na cokole otoczonym przez postacie i atrybuty symboliczne
Keywords: chorographic maps; political-administrative maps; street maps; Wrocław street maps; Silesia; 18th century

Západní rusko a přilehlé části říše německé a rakousko-uherska - Machát, František (1876–1935). Oprac. (Nákladem umĕleckého ústavu grafického V. Neuberta, 1914)
Scale 1:1 250 000
1 map : lithogr., col. ; 66x76 cm, on sheet 68x82 cm
Without legend of map
Date of publication from NKP online
Keywords: chorographic maps; political-administrative maps; Central Europe; 20th century

Mapa Zagłębia Dąbrowskiego i okolic (Lit. Bogdański, Trenner i Ska, 1911)
Scale [1:50 000]
1 map : lithogr. ; 62x53 cm, on sheet 69x57 cm
Prime meridian Ferro
Keywords: topographical maps; economic maps; Dąbrowskie Coalfield; 20th century

O Pusczy Białowiezkiéy i o celnieyszych w niéy zwiérzętach czyli Zdanie sprawy z polowaniá odbytego w dniach 15 i 16 lutego r. b. na dwa zubry [...]. - Jarocki, Feliks Paweł (1790–1869). Autor ([wydawca nieznany], 1830)
zubr (European bison)
Pages [1], 232-281, [1] ; 21 cm
Nadbitka: Pisma rozmaite wiérszem i prozą Felixa Pawła Jarockiego. T. 2
Keywords: Tsar Nicolas I; hunting; personal relations; travels; geographical descriptions; Białowieża Forest

Podróż koleją Syberyjską na Daleki Wschód : z ilustracjami (Wydawnictwo Stanisława Bukatego, 1904)
Scale [ca 1:4 000 000]
Scale [ca 1:4 700 000]
2 maps on 1 sheet ; 19x187 cm, 18x35 cm, on sheet 19x223 cm, folded in cover 19x19 cm
No legend, on the reverse sheet photo
Additional information on the cover: Dozvoleno Cenzuroû Varšava, 4 Marta 1904 g. ; Druk B. A. Bukaty, Wspólna 48
Keywords: transport maps; railway maps; Russia; Siberia; China; Manduria; Transsiberian Railway

Przegląd Geograficzny T. 53 z. 3 (1981) (IGiPZ PAN, 1981)
24 cm
Keywords: railway network diffusion; centrographic measures; gravitational methods; graph methods; hierarchy of spatial units; intervoivodship migration; tills; steppe vegetaton; radiation balance; springs; Lublin Upland; shape of settlement units; philosophical patterns of geography; sylvan ecosystems; acid rain; landscape maps; economic geography; Siberia; Mongolia; Poland

Przegląd Geograficzny T. 58 z. 1-2 (1986) (IGiPZ PAN, 1986)
24 cm
Keywords: geomorphological divisions; land use; runoff; soil erosion; flysch slopes; denudation; fluvial transport; landslides; energy circulation; behavioural geography; perception of urban space; productive agricultural space; grasslands; soil temperature; Europe; Warsaw; Poland; Beskidy Mountains; Carpathians

Przegląd Geograficzny T. 67 z. 1-2 (1995) (IGiPZ PAN, 1995)
24 cm
Keywords: urban systems; theory of geography; regional geography; bioclimate; transport infrastructure; anthropogenic changes of relief; transb-border transportation; sustainable development; landscape; anthropopression; ecologically threatend areas; water conditions; geomorphology; ice-morainic ramparts; extreme floods; Poland; Wałbrzych Basin; Poznań; Spitsbergen; Gobi Desert

Przegląd Geograficzny T. 63 z. 1-2 (1991) (IGiPZ PAN, 1991)
24 cm
Keywords: cultural space; agricultural towns; bioclimate; typologies of bioclimate; radiation-effective temperature; lacustrine sediments; pumped storage power station; telecommunications; floodplains erosion; human body heat balance; deglaciation; polar glaciers; Gościąż Lake; Żarnowieckie Lake; Sptisbergen; Poland

Przegląd Geograficzny T. 78 z. 1 (2006) (IGiPZ PAN, 2006)
24 cm
Keywords: troposphere; jet streaks; geodiversity; landscape indicators; bifurcated flow; tills; fluvioglacial deposits; patterned grounds; coal mining; anthropogenic relief; European Pond Turtle; Europe; Poland; Germany; Vistula River; Toruń Basin; Wałbrzych; Polesie National Park

Szopotzkin, Porjetschje, Grodno (West), Grodno (Ost), Sokołka, Indura / Bearbeitet in der Kartogr. Abteilung des Stellvertretenden Generalstabes der Armee - Niemcy. Heer. Generalstab. Kartographische Abteilung. (s.n.], 1915)
Skala 1:100 000
1 mapa : kolor. ; 85x68 cm, na ark. 106x72 cm
Arkusz zbiorczy zawiera 6 arkuszy mapy seryjnej Karte des westliche Russlands : 1:100 000: N 26 Szopotzkin, O 26 Porjetschje, N 27 Grodno (West), O 27 Grodno (Ost), N 28 Sokołka, O 28 Indura
Południk zerowy Ferro
Na dolnym marginesie 2 podziałki liniowe, legenda i zasady polskiej wymowy
Keywords: topographical maps; West Russia; East Europe; Belarus; Grodno region; Sokółka region

Offizielle Wegekarte vom Riesen-, Iser-und Jeschkengebirge, mit den farbig bezeichneten Wanderwegen : Im Auftrage des Deutschen und Österreichischen Riesengebirge-Vereins sowie des Deutschen Gebirge-Vereins für das Jeschken-und Isergebirge - Baron, Paul. Oprac. (Verlag von Max Leipelt, 1914)
Scale 1:130 000
1 map : lithogr., col. ; 45x63cm, on sheet 49x70cm, folded to 20x10cm
Map title
Date of publication on panel: 1914/15
Cited in: Historia nowożytna kartografii Śląska 1800-1939 / Henryk Kot. - Katowice, 1970. item 334, p. 179
Keywords: tourist maps; Giant Mountains; Jizera Mountains; 20th century